Lower Serum Vitamin D Metabolite Levels in Relation to Circulating Cytokines/Chemokines and Metabolic Hormones in Pregnant Women with Hypertensive Disorders - Adela, Ramu; Borkar, Roshan M.; Mishra, Navneeta; Bhandi, Murali Mohan; Vishwakarma, Gayatri; Varma, B. Aparna; Ragampeta, Srinivas; Banerjee, Sanjay K. (Frontiers in Immunology, 2017)
The aim of this study was to investigate whether lower serum vitamin D metabolite levels were associated with altered cytokine/chemokine and metabolic hormone levels in three different hypertensive disorders in pregnancy (HDP). Healthy pregnancy (n = 30) and hypertensive disorders in pregnancy (HDP) (n = 30), i.e., gestational hypertension (GH), preeclampsia (PE), and eclampsia (EC) subjects were enrolled. Vitamin D metabolites were measured by UPLC/APCI/HRMS method. Circulatory 27 cytokines/chemokines and 10 metabolic hormones were measured. Significantly decreased 25(OH)D and 1,25(OH)2D levels were observed in HDP. The levels of 25(OH)D were significantly lower in PE and EC, whereas the serum levels of 1,25(OH)2D significantly decreased only in EC subjects. Serum 25(OH)D and 1,25(OH)2D levels were negatively correlated with systolic- and diastolic blood pressure, creatinine, and uric acid levels. Serum interleukin (IL)-6 and IL-13 decreased, and GIP levels were increased in gestational hypertensive subjects. Platelet-derived growth factor-BB and IL-8 levels were increased and macrophage inflammatory protein-1beta levels were decreased in EC subjects. IL-8 and IL-10 increased, and rantes and GIP levels decreased in the EC group as compared with the GH group. Multivariate logistic regression analysis showed that eotaxin, monocyte chemotactic protein-1, 25(OH)D, and 1,25(OH)2D were predictors of HDP. Our analyses suggest that lower vitamin D metabolites are associated with altered cytokines/chemokines and metabolic hormones in HDP.